PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII MTS: Pemecahan Masalah Matematis - Liati, Putri; Ediputra, Kasman; Zulfah, Zulfah (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
This research was aimed to determine whether there is an effect of applying the Problem Based Learning model on mathematical problem solving abilities. The formulation of the problem in this study is whether there is an effect of applying the Problem Based Learning model on mathematical problem solving abilities?. Therefore, tcount > ttable (7,262 > 2,000) so that Ho is rejected and Ha is accepted. In addition, the experimental class mean was reached 82.286 which is higher than the control class mean was reached 62.171. Based on the results of the analysis, it can be seen that there are differences in the mathematical problem solving abilities of students who use the Problem Based Learning model with students who learn to use conventional learning. With these differences, it can be concluded that there are differences in mathematical problem solving abilities between students who learn to use the Problem Based Learning Model and students who learn to use conventional learning by class VIII students at MTs.S Balung. Keywords: quasi-experimental research, Learning model, mathematical problem solving